Evaluasi dan Pengembangan Model Tata Kelola TI dengan Kerangka Kerja COBIT 5 Domain APO10 dan DSS01 - Roni Yunis; Putri Nurul Adinda; Rumada Yulan Manurung; Angela - (Fakultas Informatika, 2018)
The IT Governance is very important for business. Many companies that have used information technology as one of the supporting factors in achieving the company's business goals, but many do not have a good governance model for alignment between business objectives and IT goals. In the study there are two problems that need to be managed properly by the company, namely the relationship with suppliers related to the system used and how to carry out operational activities and procedures needed to provide internal and outsourced IT services. The two problems will be discussed in the form of case studies using the COBIT 5 framework. COBIT 5 is a framework that covers all aspects contained in information technology governance. The domain in COBIT 5 that can answer these problems is the Manage Supplier (APO10) domain that deals with Manage Operational (DSS01) that are related to the organization's operational management. The purpose of this study is to find the level of capability, and the gap value (gap) obtained through a comparison between the target value to be achieved by the company (to be) and the value of the capability of the company today (as is). The results of the gap values obtained will be used as a basis for making recommendations for improvements, and the governance models required by the company.